Denial and Empathy: Partners in Employee Trust Repair? - Bagdasarov, Zhanna; Connelly, Shane; Johnson, James F. (Frontiers in Psychology, 2019)
Prior research on trust repair has focused primarily on investigating verbal responses to breaches of trust. Although consistently implicated in violations, the role of affect in the repair process has been mostly ignored. Using a scenario-based paradigm, we conducted an experimental study to examine the value of violator empathy, specific responses to an integrity-based violation (apology vs. denial), and nature of consequences (personal vs. organizational), as well as their interactive effects, on trust repair. Consequently, we sought to merge work on verbal responses with affect. Major findings indicated that presence of violator empathy functioned to repair trust better than its absence and, when coupled with a denial of culpability, produced markedly increased perceptions of violator’s integrity. These findings contribute to our understanding of how leaders influence followers through affect, informing both emotion and trust theory.